Analysis Of The Effect Of Sedimentation On The Capacity And Performance Of Drainage Channels On The Kapten M. Jamil Lubis–Peringgan Medan Road Section - Paulus Franklyn Marihot Hutasoit; Jahari Silaban; Yuni Yolanda (CV. SINAR HOWUHOWU, 2026)
Urban drainage systems play a crucial role in controlling stormwater runoff and preventing flooding. However, drainage channel performance often declines due to sedimentation and increased flow loads. This study aims to analyze the effect of sedimentation on the capacity and performance of drainage channels on the Jalan Kapten M. Jamil Lubis to Jalan Peringgan section in Medan City. The methods used included hydrological analysis to determine runoff discharge based on rainfall return periods (2, 5, 10, 25, and 100 years), measuring the dimensions of existing channels, and calculating sedimentation volume and channel capacity. The results showed that the total sedimentation volume reached approximately 1,359.63 m³, with an average decrease in channel capacity of 17.49%. Runoff discharge increased with increasing rainfall return periods, from 0.171 m³/s at a 2-year return period to 0.246 m³/s at a 100-year return period. This indicates that the existing channel capacity is beginning to suboptimally accommodate the design discharge, especially at medium to high return periods. Furthermore, population growth has increased the burden of domestic waste entering drainage channels. Based on the analysis, mitigation efforts are needed, including routine maintenance through sediment dredging, increasing channel capacity, and implementing a sustainable drainage system to reduce runoff. With proper management, it is hoped that drainage system performance can be improved and the risk of flooding can be minimized.